Pemanfaatan Media Sosial sebagai Alat Kolaboratif dalam Proses Pembelajaran Bahasa Inggris di STIE Ganesha - Hajarudin Hajarudin (Journal on Education, 2023)
This study aims to investigate the utilization of social media as a collaborative tool in the English learning process at STIE Ganesha. The research method used is a qualitative approach with a focus on case studies. The research was conducted for six months by collecting data through participatory observation, in-depth interviews, and content analysis of interactions on social media involved in English learning. The results show that the use of social media in English learning encourages collaboration between students, increases active participation, and stimulates project-based learning. Social media also creates a supportive environment for self-directed learning and provides space for the development of communication skills in English outside the classroom. The limitations of the study include limitations in generalizing the results to a wider population and focus on the STIE Ganesha environment. The implication of this study is the need for a diverse approach to English language learning that includes the use of social media as a collaborative tool.